The Position of Culture in Elt in Indonesia - Fikri Yansyah (LINGUA: Jurnal Bahasa dan Sastra, 2020)
Abstract: The teaching of English language in the 21st century will always be tied with the cultural aspects as language and culture are inseparable. The objective of this study was to fid out students’ perception towards the position of culture in ELT in Indonesia. The research participants were 100 students of English Education Study Program of Islamic State University Raden Fatah Palembang that were chosen randomly. Questionnaires and interviews were employed as methods in obtaining the data. The result of the study showed that the prospective English teachers in Indonesia realized the important position of culture in ELT in Indonesia.Keywords: culture, perception, culture in ELT in IndonesiaAbstrak: Pengajaran bahasa Inggris di abad ke-21 akan selalu berhubungan erat dengan aspek kebudayaan sebagaimana bahasa dan budaya merupakan satu-kesatuan. Artikel ini bertujuan mencari tahu persepsi siswa terhadap posisi budaya dalam pembelajaran bahasa Inggris di Indonesia. Subyek dari penelitian ini adalah 100 mahasiswa Pendidikan Bahasa Inggris UIN Raden Fatah Palembang yang dipilih secara acak. Dalam penelitian ini, angket dan juga wawancara digunakan untuk memperoleh data. Dari penelitian ini didapatkan bahwa calon guru bahasa Inggris di Indonesia menyadari pentingnya peran budaya dalam pembelajaran bahasa Inggris di Indonesia.Kata-kata kunci: budaya, persepsi, budaya dalam pembelajaran bahasa Inggris di Indonesia